2010
DOI: 10.1016/j.ejcts.2009.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation following 107 days of extracorporeal membrane oxygenation

Abstract: Severe adult respiratory distress syndrome (ARDS) is associated with failure to maintain adequate gas exchange. There is increasing success using extracorporeal membrane oxygenation (ECMO) for respiratory failure; the longest reported surviving patient has been supported by ECMO for 57 days. At best about 50% wean from ECMO and should weaning fail their course is fatal. ECMO is generally considered to be a contraindication for successful lung transplantation. This report describes a patient maintained on ECMO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 10 publications
0
38
1
Order By: Relevance
“…In 2010, our group reported a 107-day bridge to transplant with venovenous ECMO in a patient with ARDS. The patient survived for 351 days after lung transplantation before dying of pneumonia [7]. Most recently, we have successfully bridged a 22-year-old female patient with postpartum ARDS to lung transplantation after 155 days of ECMO support [8].…”
Section: Commentmentioning
confidence: 97%
“…In 2010, our group reported a 107-day bridge to transplant with venovenous ECMO in a patient with ARDS. The patient survived for 351 days after lung transplantation before dying of pneumonia [7]. Most recently, we have successfully bridged a 22-year-old female patient with postpartum ARDS to lung transplantation after 155 days of ECMO support [8].…”
Section: Commentmentioning
confidence: 97%
“…The importance of pulmonary support by veno-venous (VV) ECMO is also underlined by the remarkable survival rates of almost 80% in patients suffering from an H1N1 infection and severe pulmonary failure [8]. Another rather new application area of ECMO is as bridge to lung transplantation where support intervals of 11-107 consecutive days have been reported [9][10][11]. However, the experience with longterm extracorporeal pulmonary support remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when valproic acid and clozapine are used together, clozapine might be a true cause of pleural effusion as demonstrated by DALY et al [14]. Clozapine-induced pleuritis was reported in one patient who was concomitantly treated with olanzapine [15]. These examples show the crucial role of thorough clinical evaluation, including drug withdrawal and re-challenge in making a causative diagnosis of druginduced pleural effusion.…”
mentioning
confidence: 87%
“…In the past, although increasingly used for adults with ventilationrefractory acute severe respiratory failure, ECMO has, in general, been considered to be a contraindication to lung transplantation [13,14]. However, there are an increasing number of reports in the literature on the use of this method as a bridge to lung transplantation in patients with a number of underlying conditions, including acute severe respiratory failure [13], acute respiratory distress syndrome [15], cystic fibrosis [16] and pulmonary hypertension [17][18][19][20]. A recent report of outcomes in 16 patients with end-stage pulmonary disease found that, in those who survived to transplantation, 1-yr post-transplant survival was 92% [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation